Drake the super-excited, overeager, in-your-face snake - Razi, Michaele (Little Bigfoot, 2023)
With growing awareness of the importance of teaching the concepts of consent and personal space at an early age, Drake the Super-Excited, Overeager, In-Your-Face Snake is perfect for families looking for ways to have a conversation with young children about boundaries, healthy communication, respect, and body autonomy. With a humorous approach and expressive, relatable characters, kids can learn about consent through this fun story. Drake is a very friendly snake, who loves to play with his friends, but he can be a little over-eager and disruptive when he joins in their play. He also loves to give big hugs, but he doesn’t always ask first, and his friends don’t always like to be hugged. When his friends become too uncomfortable with his hugs and no longer want to play with him, Drake realizes he needs to find other ways to approach showing his affection and engaging in play. Will Drake learn how to show his affection and how to ask to join in playtime without making his friends uncomfortable? Find out in this endearing book that addresses the importance of consent in an empathetic, positive, and kid-friendly way.